Aeromedical retrievals of people for mental health care and the low level of clinical support in rural and remote Australia. Issue 8 (25th July 2019) - Gardiner, Fergus W; Coleman, Mathew; Teoh, Narcissus; Harwood, Abby; Coffee, Neil T; Gale, Lauren; Bishop, Lara; Laverty, Martin
Abstract: Objectives: To characterise the people retrieved by the Royal Flying Doctor Service (RFDS) for treatment of mental and behavioural disorders, and to assess mental health care provision in rural and remote areas. Design: Prospective review of routinely collected RFDS and Health Direct data. Setting, participants: RFDS aeromedical retrievals of patients from anywhere in Australia except Tasmania during 1 July 2014 – 30 June 2017 for the treatment of mental or behavioural disorders. Main outcome measures: Retrievals by ICD‐10 mental and behavioural disorder diagnoses. Results: 2257 patients were retrieved by the RFDS for treatment of mental or behavioural disorders, including 1394 males (62%) and 863 females (38%); 60% of patients were under 40 years of age, 35% identified as Indigenous Australians. The most frequent mental and behavioural disorders were schizophrenia (227 retrievals, 16.5% of retrievals with ICD diagnoses), bipolar affective disorder (185, 13.5%), and depressive episodes (153, 11.2%). Psychoactive substance misuse triggered 194 retrievals (14.2%), including misuse of multiple drugs (85, 6.2%), alcohol (61, 4.5%), and cannabinoids (25, 1.8%). The mean age of patients retrieved for treatment of substance misuse (29.6 years; SD, 11.6 years) was lower than for retrieved patients overall (37.0 years; SD, 19.3 years); 38 of 194 patients retrieved after psychoactive substance misuse (19.6%) were under 19 years of age. Most retrieval sites were rural and remote communities with low levels of mental health care support. Conclusion: Mental and behavioural disorders are an important problem in rural and remote communities, and acute presentations trigger a considerable number of RFDS retrievals.